2009
DOI: 10.1097/bpo.0b013e3181c0494f
|View full text |Cite
|
Sign up to set email alerts
|

The Gross Motor Function Classification System for Cerebral Palsy and Single-event Multilevel Surgery: Is There a Relationship Between Level of Function and Intervention Over Time?

Abstract: Retrospective Study by Review of Medical Records. Level III in the Therapeutic Study investigating results of treatment category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
2
20
0
6
Order By: Relevance
“…3,7 However, recent outcome studies have reported improvement in GMFCS level in the majority of patients, by one, two or even three levels. [14][15][16]32 These reports include changes after selective dorsal rhizotomy and orthopaedic surgery. 33 However, most of these studies had methodological problems, including retrospective assignment of GMFCS level, sometimes from chart review, or a lack of supporting data from simultaneous measurements of either gait or gross motor function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,7 However, recent outcome studies have reported improvement in GMFCS level in the majority of patients, by one, two or even three levels. [14][15][16]32 These reports include changes after selective dorsal rhizotomy and orthopaedic surgery. 33 However, most of these studies had methodological problems, including retrospective assignment of GMFCS level, sometimes from chart review, or a lack of supporting data from simultaneous measurements of either gait or gross motor function.…”
mentioning
confidence: 99%
“…13 However, other studies using the GMFCS as an outcome measure after orthopaedic surgery reported that the majority of the study participants improved by one level and that some participants improved by two or three levels. [14][15][16] In one of the studies, GMFCS levels were assigned retrospectively by chart review. To date there have been few intervention studies which have reported prospectively assigned GMFCS levels and objective measures of gait and function.…”
mentioning
confidence: 99%
“…Следует отметить, что среднее коли-чество хирургических процедур на одну операцию соста-вило 4,68, это близко к данным E. Godwin и соавт. [32], которые приводят среднее количество процедур на опера-цию при одномоментных многоуровневых вмешатель-ствах -5,45.…”
Section: Discussionunclassified
“…При общем согласии в отношении многоуровневых одномоментных вмешательств существуют тем не менее различия в выборе оптимального возраста их выполне-ния: некоторые авторы предлагают хирургические вмеша-тельства у детей младшего возраста -4-6 лет [6,32], дру-гие -в возрасте 8-12 лет [7,13,26,33]. В нашем исследо-вании возраст пациентов варьировал от 5 до 17 лет, и мы полагаем, что начало оперативного лечения детермини-ровано в первую очередь развитием ортопедических ос-ложнений, возникновение которых зависит от эффектив-ности проведения профилактического медикаментозно-го, физиотерапевтического и консервативного ортопеди-ческого лечения.…”
Section: Discussionunclassified
“…Clinicians providing advice in the area of single-event multilevel surgery for children with cerebral palsy continue to deal with limitations in the literature including small study size, incomplete description of the population, retrospective design, 5 and conflicting outcomes. 6,7 Generalizing results to provide clinical guidance is therefore still challenging. This study by Rutz et al focuses on mobility outcome analysis in a specific population of children with bilateral spastic cerebral palsy (GMFCS levels II and III).…”
mentioning
confidence: 99%